2020
DOI: 10.18517/ijaseit.10.2.5839
|View full text |Cite
|
Sign up to set email alerts
|

Success Factors for Public-Private Partnership Infrastructure Projects in Vietnam

Abstract: Infrastructure projects require a great amount of capital investment resulting from their tremendous size, complexity, and risk. Due to the limitation of public finances, the private sector is invited to participate in infrastructure project development. The private sector can entirely or partially invest in an infrastructure project in the form of a public-private partnership (PPP) scheme, which has been an attractive option for several developing countries, including Vietnam. Unfortunately, despite the PPP s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…The Vietnamese economy shows growth overcoming obstacles and challenges [16][17][18]. This is partially due to the research successes of the construction and engineering material segments [19][20][21][22]. This paper showed that barite mortar's consistency is higher than standard mortar's when sand is replaced with barite powder in percentages up to 30%.…”
Section: Discussionmentioning
confidence: 99%
“…The Vietnamese economy shows growth overcoming obstacles and challenges [16][17][18]. This is partially due to the research successes of the construction and engineering material segments [19][20][21][22]. This paper showed that barite mortar's consistency is higher than standard mortar's when sand is replaced with barite powder in percentages up to 30%.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the industrialization and urbanization of a significant part of the construction industry [3]. However, due to cost overruns, many civil and infrastructure projects have been failures [4], [5]. In the construction industry, projects are characteristically enormous requiring major capital outlays.…”
Section: Introductionmentioning
confidence: 99%
“…According to the number of reports, Vietnam's economy has shown strong growth in 2019÷2020. This is the effect of continuous high domestic demand, manufacturing enterprises growth and diversity in developing industries (Dhar, 2021;Nguyen et al, 2020a;2020b). Despite the impact of recent pandemic circumstances Vietnam is considered to become the fastest growing economy in the South East Asia region (Seah, 2021;Nguyen, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…This is the effect of continuous high domestic demand, manufacturing enterprises growth and diversity in developing industries (Dhar, 2021;Nguyen et al, 2020a;2020b). Despite the impact of recent pandemic circumstances Vietnam is considered to become the fastest growing economy in the South East Asia region (Seah, 2021;Nguyen, 2020b). To be able to follow an ongoing development many challenges will have to be faced.…”
Section: Introductionmentioning
confidence: 99%